Finance and Development, June 1983. (Finance and Development; Finance and Development ;, 1983)
This paper discusses quantitative indicators that measure such macroeconomic variables as the growth of national product, inflation. The importance of considering several indicators in a dynamic context becomes particularly relevant during periods when needed economic and financial adjustment measures are undertaken. Rationales given for maintaining negative real interest rates in developing countries range from keeping down the cost of servicing the public sector's debt, or of investment, to avoiding the consequences of other policies.